PENGARUH KONSENTRASI DAN METABOLIK SEKUNDER Trichoderma harzianum TERHADAP PENGENDALIAN PENYAKIT BLAS, PERTUMBUHAN DAN PRODUKSI TANAMAN PADI (Oryza sativa L.) - Pramono Hadi; Dodi Suyanto; Shalahudin Mukti Prabowo; Srie Juli Rachmawatie (Agriculture faculty, Darul ‘Ulum Islamic University (UNISDA) of Lamongan, 2022)
The aim of this research was to know the influence Trichoderma harzianum and Trichoderma harzianum metabolic secunder concentration to growth, yield and to bridle of blas attack at rice plant. This research have been conducted on November 10th 2021 until January 12th 2022 in seeding of breeding, fish and made insiminasi Begajah village, Sukoharjo Subdistrik, Sukoharjo regency, at Regosol soil type with the place hight 120 meters above the sea level. This research represent the factorial attempt use Randomized Completely Design (RCD), consisted of two treatment and three replications. The first factor were Trichoderma harzianum concentration (T), consisted of three level (T0 = 0 cc/l, T1 = 10 cc/l and T2 = 20 cc/l). The second factor were Trichoderma harzianum metabolic secunder concentration (M) consisted of three level (M0 = 0 cc/l, M1 = 10 cc/l and M2 = 20 g/l). The result of this research showed was : Trichoderma harzianum Concentration treatment significant toward height of plant, dry weight of crown, very significant toward blas attack intensity, fresh weight of crown, dry weight of harvesting grain per stool and was not significant toward weight of 1000 grain. Trichoderma harzianum metabolic secunder Concentration treatment significant toward height of plant, dry weight of crown, very significant toward blas attack intensity, fresh weight of crown, dry weight of harvesting grain per stool and was not significant toward weight of 1000 grain. Interaction between Trichoderma harzianum and Trichoderma harzianum metabolic secunder concentration treatment was not significant toward of all parameters. The blas attack intensity lowest 4,49%, mached from treatment combination T2M2 (to gift of Trichoderma harzianum concentration at 20 cc/l and Trichoderma harzianum metabolic secunder concentration at 20 cc/l), can to produce dry weight of harvesting grain highest 41,29 g/stool. The blas attack intensity highest 45,68%, mached from treatment combination T0M0 (without to gift of Trichoderma harzianum and without to gift of Trichoderma harzianum metabolic secunder concentration), can to produce dry weight of harvesting grain lowest 29,11 g/stool.